THE INFLUENCE OF THE AUTOMATED SHORT ESSACCORING (ASES) ASSESSMENT MODEL IN MEASURING THE INTEGRATION OF STUDENT CHARACTER VALUE - Evi Susilawati (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine the influence of using the Automated Short Essay Scoring (ASES) assessment model on the integration of character values in the Teaching and Education Faculty of the Universitas Islam Sumatera Utara. This type of research is quasi-experimental. The population of this study were all fifth semester students of the Teaching and Education Faculty (FKIP) of the Islamic University of North Sumatra (UISU), totaling 70 students. This study used a random sampling technique, namely classes were conducted randomly so that the research sample was obtained from Semester V students of the History Study Program, totaling 13 students as the experimental class, and Semester V students of the Pancasila and Citizenship Study Program. totaling 15 students. as control class. The data collection method used is the test method. The collected data were analyzed using inferential statistical analysis (t-test). Based on data analysis, it is known that there is an influence of using the Automated Short Essay Scoring (ASES) assessment model on the integration of student character values